Structural and dielectrical properties of PMMA/TiO2 composites in terms of free volume defects probed by positron annihilation lifetime spectroscopy - TAV, CUMALİ; ESMER, KADİR; YENER, MEHMET DENİZ; YAHŞİ, UĞUR (SAGE PUBLICATIONS LTD, 2021)
A suspension of ultrasonically agitated Titanium dioxide micrometer-sized powder has been introduced into a poly(methyl methacrylate) (PMMA) matrix by solvent (CHCl3) mixing under slow mechanical stirring, and the resulting suspension was used to cast free-standing PMMA/TiO2 composite films. Filler contents from 0 wt% to 7.5 wt% were selected, since TiO2 particles could not be previously suspended in chloroform at higher concentrations by ultrasonic agitation. Optical and dielectric properties of composites were determined by ultraviolet (UV)-visible and dielectric spectrometry. In the UV region, 450% improvement of UV absorption was achieved in the TiO2/PMMA composite compared with neat PMMA. The structural properties and hole-free volume of the composites were determined by X-ray diffractometry and positron annihilation lifetime spectroscopy, respectively. The particle size and homogeneous dispersion of the particles in the polymer matrix were related to the hole-free volume of the PMMA.
Keywords: PMMA; TiO2; composite; dielectric properties; UV-visible; free volume; positron annihilation lifetime spectroscopy